Republic of Equatorial Guinea : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Equatorial Guinea. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Equatorial Guinea's recent economic performance has been weak, notwithstanding the high-quality infrastructure that has been built. The current account deficit has progressively increased to about 10 percent of GDP by 2014 as a result of lower exports from maturing hydrocarbon fields combined with high import levels associated with the public infrastructure program, although there is considerable uncertainty about this figure given very weak external sector statistics. The main near-term risk to the economic outlook is a slower-than-expected fiscal adjustment that could result in the depletion of fiscal buffers and accumulation of public debt. Moreover, an insufficient effort to address a weak business climate and attract foreign investment would impede diversification and potential nonhydrocarbon growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet